Advantages and perspectives of using medicines in the form of auto injectors and prefilled syringes - N. V. Sholoyko; A. O. Gonchar; T. I. Lysenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Today, there is a need to introduce medical devices into everyday medical practice with the goal to self-administer injectional drugs. The speed and safety of auto-injectors / pre-filled syringe pens use (AI/PFS) is the introduction of an injectional form drug in a special medical device, which allows patients to enter a pre-designated therapeutic dose due to the characteristics of the structure of the product, automatic dosing, data of the interactive display on some devices, comfortable design, etc. Considering that AI/PFS were developed to improve the quality of life of patients with various pathological conditions, therefore the creation of affordable medical devices for low-income groups of the population is relevant today. Also an actual issue is the provision of high-quality first-aid kits for soldiers, which is a vital component for medical care in the context of active combat conditions and the lack of the required number of field hospitals.The speed of administration, the onset of effect and ease of use provides significant advantages for AI / PFS. Therefore, the issue of affordability for the low-income groups of the population and the army with the necessary drugs should be sufficiently supported by state regulation.Purpose of study - study of the international experience in the implementation and use of drugs (drugs) in the form of affordable, safe and effective modern dosage forms in the form of autoinjectors.Materials and methods - foreign and domestic literature on the use of AI/PFS in complex and monotherapy treatment of various diseases. State registries of medicines of Ukraine, the USA and some EU countries. The study used systematic, statistical and comparative analyzes, as well as the generalization of information. The data used is freely available among various medical scientific and metric bases, the Internet and international scientific conferences.The analysis of the use of AI/PFS indicates that today the world market of medicines and medical devices contains a large number of drugs under different trade names. However, many patients in the world refrain from using these dosage forms due to the significant cost of medical devices, which makes impossible the required regular use of such drugs for the low-income population groups. This is a significant disadvantage, since AI / PFS is implemented to correct not only chronic diseases such as rheumatoid arthritis, multiple sclerosis, but also to provide emergency careinurgent conditions (anaphylactic reactions, intense pain, etc.).In the global market for drugs and medical devices, injectable medicines in the form of AI/PFS are widely represented. The effectiveness of the use of such devices indicates the advantages and prospects for the use of existing AI/PFS on the global market for patients and medical personnel. Today, the most commonly used drugs in AI/PFSare for the treatment of diabetes, emergency conditions in civil and military medicine, chronic diseases of various etiologies, pediatric practice. The use of AI /PFS significantly improves patient compliance for the treatment of chronic diseases due to ease of use and reduction of adverse reactions at the site of administration. Most of the analyzed sources indicate a low level of economic affordability of drugs in the form of AI/PFS for the population and the government sector of drug supply due to the high cost of the medical devices, compared to traditional syringes. But the results of the study indicate a high level of advantages and prospects in the use of drugs in AI/PFS in medical practice for both medical personnel and patients.